PARTISIPASI KAUM PEREMPUAN DALAM PERENCANAAN PENGELOLAAN DANA DESA - Nurhalimah, Andi; edison, edison (Jurnal Ilmu Administrasi Negara (JUAN), 2018)
This study discusses the Participation of Women in Village Fund Planning and Management. The purpose of this research is to find out how the participation of women in planning and management is involved in the Village of Medicine. The informants in this study were 20 (twenty) speakers from 3 (three) Village Governments, 5 (five) PKK people, 3 (three) Posyandu people, 8 (eight) RTs, and 1 (one) KUBE person. The research method used is descriptive method of qualitative approach. The research instrument used was interviews, observation and documentation. The results of this study indicate that women's participation in village fund planning and management in Berakit Village is at the level of delegated power, placation and consultation. What is dominant in the large tokenism group is that a level of participation in the community is heard and allowed to argue, but they must not have the ability to be guaranteed that their views are considered by the power holders. And seen from the use of the village budget for gender equality in the Berakit Village is not effective and efficient. In katakana it is not effective because the selection of the type of training where the culinary made from mangroves the material used is difficult to find and not efficient because the funds are spent in large quantities but no results are returned (outcome).